Analisis Penerimaan dan Kesuksesan Implementasi E-Learning Universitas Brawijaya pada Aspek Intention to Use, Use, User Satisfaction dan Net Benefits - Deni Nugraheni; Mochamad Chandra Saputra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
University of Brawijaya Malang has applied moodle based e-learning. UB e-learning website can be accessed through vlm.ub.ac.id. This research has a purpose to determine what factors that affecting the acceptance and success of UB e-learning implementation on the aspects of intention to use, use, user satisfaction and net benefit. The model that used there are the combined model of four variables Unified Theory of Acceptance and Use of Technology (UTAUT), there are performance expectancy, effort expectancy, social influence, facilitating conditions and seven variables Delone and McLean with modifications there are system quality, information quality, service quality, intention to use, use, user satisfaction and net benefits using parametric and non parametric methods. Collecting data method using the questionnaire online, with the minimum number of samples using slovin formula of 100. Based on the results of the data that has been collected, the number of respondent that will be used for this research is 113. The collected data is tested the basic assumption of normality, linearity and homogeneity. The data that passed the basic assumption test was done by parametric analysis using simple linear regression, while those did not pass the basic assumption be analyze using non parametric using Kendall Tau method. The results showing that all the variables that checked thoroughly positively affect the aspects of intention to use, use, user satisfaction and net benefits of UB e-learning.